2017
DOI: 10.1209/0295-5075/118/37003
|View full text |Cite
|
Sign up to set email alerts
|

Possible Fano resonance for high-Tc multi-gap superconductivity in p-Terphenyl doped by K at the Lifshitz transition

Abstract: Theories and models of superconducting state PACS 74.10.+v -Occurrence, potential candidates * * * This work has been supported by superstripes-onlus. Discussions with

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 67 publications
3
67
0
Order By: Relevance
“…Moreover, they allow us to prevent radiation damage on biological samples providing new key information [70][71][72]. In this work, we present some relevant results showing the relationship between new geometries developing at nano/mesoscale and the emerging macroscopic properties in complex and heterogeneous systems in different fields opening new fundaments in natural sciences [73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they allow us to prevent radiation damage on biological samples providing new key information [70][71][72]. In this work, we present some relevant results showing the relationship between new geometries developing at nano/mesoscale and the emerging macroscopic properties in complex and heterogeneous systems in different fields opening new fundaments in natural sciences [73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…Using different procedures of alkali doping it has been recently found that p-Terphenyl K x C 18 H 14 shows a transition from an insulating transparent phase to an inhomogeneous metallic black phase which shows a superconductive behavior with critical temperature T c ranging from few degrees up to 123 Kelvin in different samples [1][2][3][4][5][6][7]. It has been proposed that the amplification of critical temperature reaching a record for metallic aromatic hydrocarbons is driven by the shape resonance belonging to the class for Fano Feshbach resonances in superconducting gaps [8]. It has been proposed that K x C 18 H 14 is a practical realization of a superlattice of quantum wires as described in several patents [9,10] where the critical temperature shows narrow dome if the chemical potential is fine tuned in the proximity of a topological electronic Lifshitz transition [11] in the conduction bands.…”
Section: Introductionmentioning
confidence: 99%
“…In this regime the Migdal approximation breakdown [76] and it is not possible to apply the BCS theory to explain the emergence of high temperature superconductivity. It has been shown that the emergence of high temperature superconductivity in a multiband scenario near a Lifshitz transition has been described by numerical solution of Bogoliubov equations [77] and can be qualitatively predicted in the limit of a steep -flat scenario [79] where the energy dispersion of the appearing band is pushed down to zero as for the case of an infinite effective mass for strong correlated localized states [78]. An essential point of this proposed scenario for the emergence of room temperature superconductivity is the theoretical demonstration that the Lifshitz transition for the appearing of a strongly correlated band is not of 2,5 order but becomes of first order with appearing of a frustrated phase separation [79], interface superconducting [80] and a hyperbolic space of filamentary pathways in two dimensional systems like it was observed in cuprate perovskite superconductors at optimal doping [81].…”
Section: Figurementioning
confidence: 99%